Dokufiktionalität in Literatur und Medien Erzählen an den Schnittstellen von Fakt und Fiktion - Bidmon, Agnes; Lubkoll, Christine (De Gruyter, 2021)
Hybrid narratives between fact and fiction are all the rage these days. Frequently, they are characterized as "docu-fiction," though it is unclear which staged references to self and others are actually covered by the concept. The interdisciplinary volume analyses the forms and functions of docu-fictional narration in literature and media and works to define the contours of the term.